2016
DOI: 10.1007/s10661-016-5573-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation behavior of octachlorodipropyl ether residues during tea planting and brewing process

Abstract: The dissipation behavior of octachlorodipropyl ether (OCDPE) residues in fresh tea shoots and in tea prepared under field conditions was investigated, and the transfer of residues from brewed tea to tea infusion was determined. OCDPE levels in tea shoots, prepared tea, tea infusion, and spent tea leaves were determined using a sensitive and simple method. The dissipation of OCDPE is fairly slow in tea shoots and prepared tea, with half-life values of 5.10 and 5.46 days, respectively. The degradation rates of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Several factors, including environmental factors (light, moisture, and pH), the crop characteristics, and physical and chemical properties of the pesticide (water solubility and volatility), have played a fundamental role in affecting pesticide persistence in crops [ 12 ]. A. polytricha was mainly cultivated in greenhouse.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors, including environmental factors (light, moisture, and pH), the crop characteristics, and physical and chemical properties of the pesticide (water solubility and volatility), have played a fundamental role in affecting pesticide persistence in crops [ 12 ]. A. polytricha was mainly cultivated in greenhouse.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al reported a decrease between 4.31% and 31.7% in the transfer rate of polycyclic aromatic hydrocarbons with increasing octanol–water partition coefficient [ 30 ]. In addition, continuous boiling and increased brewing times can lead to a higher transfer of pesticides into the tea infusion [ 12 ]. As reported by Ozbey and Uygun [ 17 ], the transfer rate of chlorpyrifos varies between 11% and 91% for brewing times between five and 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is also evidence that pesticides can be transferred from the tea matrix to the infusion during preparation [ 10 ]. The transfer rates of several kinds of pesticides, such as pyrethroids, organophosphorus compounds, neonicotinoids, carbamates, and benzoylurea, have been reported in the range from 0 to 85% [ 11 , 12 ]. Whereas most studies have focused on the transfer of pesticides from green tea or black tea [ 13 ] to infusions, only limited information is available on the transfer of pesticide residues from herbal tea.…”
Section: Introductionmentioning
confidence: 99%
“…19 To the best of our knowledge, scarcely any studies about the simultaneous determination of tolfenpyrad, dinotefuran and its metabolites in tea have been reported to date. Furthermore, although research has been carried out on the dissipation of pesticides during tea planting, processing and brewing, 1,3,4,[20][21][22][23][24] scarcely any literature has reported in the residue behavior and brewing transfer of tolfenpyrad, dinotefuran and its metabolites in tea. Therefore, it is significant to establish a reliable method for the simultaneous determination of tolfenpyrad, dinotefuran and its metabolites in tea, and use this to investigate their behavior during tea growth and tea brewing.…”
Section: Introductionmentioning
confidence: 99%